Peningkatan Hasil Belajar Matematika Siswa Melalui Inquiry-Based Learning Berbantuan Flipped Classroom Berbasis Kemandirian Belajar Siswa UPT SPF SD Negeri 101807 Candirejo - Khairunnisa, Rizkia; Hasratuddin; Ardi Dwi Susandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve students' mathematics learning outcomes through the application of an Inquiry-Based Learning model assisted by a Flipped Classroom based on student learning independence at UPT SPF SD Negeri 101807 Candirejo. The main problem in this study is the low mathematics learning outcomes caused by a lack of independent learning activities and teacher-centered learning. Through a combination of Inquiry-Based Learning and Flipped Classroom, it is hoped that students can be more active, independent, and have a better conceptual understanding. This study used a quantitative approach with a quasi-experimental method and a randomized pretest-post test control group design. The research subjects consisted of two classes, namely the experimental class that received treatment with the Inquiry-Based Learning model assisted by the Flipped Classroom and the control class that used conventional learning. Data were collected through mathematics achievement tests and learning independence questionnaires. The results showed that there was an increase in the mathematics achievement of students taught with Inquiry-Based Learning assisted by the flipped classroom compared to conventional learning with a sig value < 0.05, namely 0.000.